Future changes of tropical cyclone activity over the west Pacific under the 1.5°C and 2°C limited warming scenarios using a detecting and tracking algorithm - Deng, Hao; Ji, Zhenming; Zhu, Xian; Dong, Wenjie (Frontiers in Environmental Science, 2022)
This study evaluates changes to the number, intensity and path of tropical cyclones (TC) in the 21st century under the 1.5 °C “never-exceed” (NE), 1.5 °C overshoot (OS), and 2.0 °C “never-exceed” (NE) limited warming scenarios, compared to the historical experiments of the Community Earth System Model Large Ensemble Project (CESM-LE). The large amount of data generated by the model makes it impossible to manually extract TC activity. A tracking algorithm was developed to detect and track TC activity. The results show that the algorithm has good stability and high accuracy, and it is suitable for grid data with spatial resolutions finer than 2.0°×2.0°. The analysis shows that changes of sea surface temperature and wind shear are responsible for the increment in the TC mean intensity under warmer scenarios. Under the 1.5 °C OS scenario, the annual mean number of TCs and mean TC energy increase the most. The power dissipation index (PDI) of TCs under three scenarios were projected significantly increased. Under the 1.5degNE and 2.0degNE scenarios, more TCs move to the northeast part of China over time. Under the 1.5degOS scenario, more TCs will land in Southeast China in the end of this century. The coastal areas of northern China may gradually become another area of dense TC landing.